K-12 Teacher Perceptions Regarding the Flipped Classroom Model for Teaching and Learning. (March 2017) - Gough, Evan; DeJong, David; Grundmeyer, Trent; Baron, Mark
A great deal of evidence can be cited from higher education literature on the effectiveness of the flipped classroom; however, very little research was discovered on the flipped classroom at the K-12 level. This study examined K-12 teachers' perceptions regarding the flipped classroom and differences in teachers' perceptions based on grade level and content area taught. A researcher-developed survey instrument was used to collect data from K-12 teachers that utilize a flipped classroom in Southwest and South Central Minnesota. Survey participants totaled 44, which included 27 high school teachers, 15 middle school teachers, and 2 teachers that identified as other . It was found that participants perceived that the flipped classroom creates time for varied instructional techniques, including active learning and higher order thinking, along with increased student-to-teacher interaction. The insights from the study inform teachers in the field about benefits and best practices in regard to the flipped classroom instructional model.